Does reduced intraspecific competition of the dominant species in intercrops allow for a higher population density? - Wang, Qi; Bai, Wei; Sun, Zhanxiang; Zhang, Dongsheng; Zhang, Yue; Wang, Ruonan; Evers, Jochem B.; Stomph, Tjeerd‐Jan; Werf, Wopke; Feng, Chen; Zhang, Lizhen (Food and energy security, 2021)
Dominant species in intercropping experience less resource competition compared with its monoculture. This reduced competition for resources may allow cultivating the dominant species at an increased density in intercropping to obtain greater yield. However, experimental results are inconclusive when the optimal within row density in the sole crop is not well established. Here, we conducted a two‐year experiment to test the hypothesis that optimal within row plant density of dominant species in intercropping would be higher in the intercrop than in the sole crop. We tested three maize densities (3, 4.5, and 6 plants m−1) in both sole maize and two replacement designed intercrops. The row configurations of two intercrops are two rows maize intercropped with four rows peanut (M2P4) and four rows maize intercropped with four rows peanut (M4P4). Peanut was grown at the same plant density of 12 plants m−1 row in both sole crop and intercrops. The results indicated that increasing maize density from the optimal density in monoculture is not worthy of promotion to improve yield in intercropping, which denied our hypothesis. The land equivalent ratios (LER) in the dry year (2017) were higher than the wet year (2016). Maize yields per unit area of the whole intercropping system were highest with densities of 4.5 and 6 plants m−1 row, with no significant difference between these two densities. Maximum maize yields in sole cropping were obtained with maize densities of 6 plants m−1 row. Intercropping provided higher yields at low and intermediate sole crop maize densities, but not at high sole crop maize density. Average land equivalent ratios at 3, 4.5, and 6 plants m−1 of maize were 1.09, 1.04, and 0.95 in 2016, and 1.07, 1.10, and 1.02 in 2017. Our results suggest that intercropping performs better at conditions with less resources than adequate resources. The current study explored whether intercropping allows increasing the density of the dominant species in terms of plants per meter row above what is optimal in sole cropping. The results demonstrating a different maize yield‐density response in intercropping with sole maize and contradict the notion that the optimal density of a dominant species is higher in intercropping than in sole cropping.